Perception of buffalo farmers towards scientific buffalo husbandry practices: applying the extended UTAUT framework - Aiswarya, Sabu; Gururaj, Makarabbi; Navneet, Saxena; Sharma, Madan Lal (Frontiers in Animal Science, 2025)
Sustainable livestock development hinges on the widespread adoption of scientific husbandry practices, particularly among smallholder farmers who are the backbone of rural animal agriculture. Despite increasing technological availability, the behavioural drivers that influence adoption remain insufficiently understood—creating a critical gap between innovation and impact. This study applies the Unified Theory of Acceptance and Use of Technology (UTAUT) and partial least squares structural equation modelling (PLS-SEM) to examine how habit (HA), performance expectancy (PE), effort expectancy (EE), and social influence (SI) shape behavioural intention (BI) and use behaviour (UB) among 530 buffalo farmers across India. Results show that habitual practices are the strongest predictor of behavioural intention (β = 0.420, p< 0.001), followed by effort expectancy (β = 0.206, p = 0.008) and performance expectancy (β = 0.156, p = 0.027). Social influence had no significant effect (β = 0.136, p = 0.133). These findings highlight that farmers prioritize compatibility with existing routines, ease of use, and visible benefits over peer or expert influence in adopting new practices. The study advances the literature on agricultural innovation by empirically validating habit as a central determinant of technology adoption in livestock systems. It offers practical insights for designing behaviourally responsive extension strategies that integrate innovations into the lived realities of farmers—thereby supporting more sustainable and scalable livestock development.